Financial stress and debt among university students: The role of Islamic financial literacy - Azman Jusoh, Mohd Kamal; Che Harun, Mohd Faizal Azrul Azwan; Mohamad, Siti Aishah; Mohamed Azudin, Muhammad Zainddin; Azemi, Mohd Azharul; Mohamed, Asjad; Mahmood, Wan Nurashikin (Journal of Islamic, Social, Economics and Development, 2025)
Effective financial management is crucial in ensuring the sustainability of students’ lives and academic achievement in higher education institutions. However, rising living costs, academic expenses, and modern lifestyle demands have significantly contributed to financial stress among students. From an Islamic perspective, financial management based on shariah principles emphasizes blessings in sustenance, prioritization of needs over wants, and the avoidance of excessive debt. Nevertheless, the application of these principles remains limited. In addition, the level of financial literacy among Malaysian youth is generally at moderate level, leaving students vulnerable to imprudent financial decisions. The study conducted with three objectives; to assess the level of Islamic financial literacy among university students to examine the factors influencing financial stress and indebtedness among students and to propose Shariah-based strategies that can strengthen students’ financial well-being. A quantitative study was employed, and a survey was conducted on 400 students of UiTM Pahang. The Statistical Package for the Social Sciences (SPSS) version 27.0 was used to analyse the data. Preliminary findings indicated that students experience high levels of financial stress due to dependence on educational loans, escalating living costs, and consumptive spending behaviours, while limited Islamic financial literacy emerged as the key factor contributing to ineffective financial management. To address these challenges, the study suggests that universities strengthen Islamic financial management modules, expand zakat assistance and shariah-compliant scholarships, as well as provide more structured financial guidance. The findings are expected to assist students in managing their finance more prudently, reduce the risk of academic attrition, and contribute to the development of financially resilient graduates grounded in Islamic principles.